Comparative human landing catch and CDC light trap in mosquito sampling in knowlesi malaria endemic areas in Peninsula Malaysia - Ahmad, Rohani; Azahary, Abd Rahman Aidil; Mohamed Nor, Zurainee; Wan Mohd Ali, Wan Najdah; Ismail, Zamree; Mohd Omar, Hanif; Mohd Majid, Ariffin; Hamid, Zuhaizam; Ismail, Suzilah; Lee, Han Lim (Scientific Research Publishing, 2016)
Adult mosquito sampling techniques are essential for monitoring transmission of malaria and other mosquito borne infections.Preference for any sampling technique depends on both its field efficiency and the characteristics of local vector populations. Surveys on adult mosquitoes using Human Landing Catch (HLC) and CO2-baited CDC light trap (CDC-LT) techniques were conducted in several knowlesi malaria endemic areas between the months of March to December 2012 in several states of Peninsula Malaysia.These two techniques were relatively compared to determine the preferences of anopheline mosquitoes towards CO2-baited CDC-LT technique using HLC technique as the reference method. Cx. gelidus, An. maculates and An. introlatus were the main three species collected by HLC technique, whereas the species collected by CO2-baited CDC-LT technique were mostly An. cracens, Ar.durhami and Coquillettidia species. Most of the Anopheles species were collected almost exclusively by the human collectors except for An. cracens and An.introlatus which were collected using both techniques.Anopheles cracens was the most dominant species captured using CO2-baited CDC-LT technique.This is the first report showing An. cracens was caught using CO2-baited CDC-LT technique in Malaysia.